2014
DOI: 10.1016/j.physbeh.2014.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Development of prenatal lateralization: Evidence from fetal mouth movements

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…In line with most previous research (Conde et al, ; de Vries et al, ; Hata et al, ; Mulder et al, ; Reissland et al, ), no differences were found between males and females in mean levels and trajectories of breathing movements. However, sex differences were found for general movements, such that male were more active than female fetuses at 21 weeks of gestation and males had a steeper decline in general movements incidence during the second half of pregnancy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with most previous research (Conde et al, ; de Vries et al, ; Hata et al, ; Mulder et al, ; Reissland et al, ), no differences were found between males and females in mean levels and trajectories of breathing movements. However, sex differences were found for general movements, such that male were more active than female fetuses at 21 weeks of gestation and males had a steeper decline in general movements incidence during the second half of pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…Fetal movements appear to be associated with a number of factors including fetal sex, gestational age at birth, and birth weight. Regarding fetal sex, the results are inconsistent, with some studies showing that male fetuses are more active than female fetuses (Almli, Ball, & Wheeler, ; DiPietro, Hodgson, Costigan, Hilton, & Johnson, ), while most studies failed to find any sex differences in fetal movements incidence (Conde et al, ; de Vries, Visser, & Prechtl, ; Hata et al, ; Mulder et al, ; Reissland, Francis, Aydin, Mason, & Exley, ; Robles de Medina, Visser, Huizink, Buitelaar, & Mulder, ). The absence of breathing movements has been identified as the best predictor of preterm birth (Boots et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…They are represented by neutral mouth movements with a decreasing frequency with advancing gestation and lateralized mouth movements, which increase in frequency with advancing gestation [38] (fig 2a).…”
Section: Facial Expressionsmentioning
confidence: 99%
“…50 Moreover, there was a significant increase in the proportion of fetal lateralized mouth openings during pregnancy, and this was also evidence of left lateralization preference in mouth movement. 51 Reissland et al 10 suggest that FOMS is more sensitive to subtle behavioral changes than KANET, which focuses on gross motor behavior. Therefore, FOMS may have a marked potential for clinical use in diagnosing abnormal fetal neurodevelopment, which KANET might fail to detect.…”
Section: Fetal Observable Movement Systemmentioning
confidence: 99%